The Effect Of Unemployment And Inflation On Economic Growth In Cirebon City 2013-2022 - Human Hanif, Sofi; fatmasari, dewi; Aziz, Abdul (Faculty of Islamic Economics and Business IAIN Syekh Nurjati Cirebon, 2024)
In Cirebon City, economic growth has experienced ups and downs in the last ten years. Where the average economic growth of Indonesia is 5.31%. Where the economy in Cirebon City always grows below the national economic growth. In the last ten years with the period 2013-2022, economic growth in Cirebon City averaged 4.47%. This study aims to see if unemployment and inflation affect economic growth in Cirebon City. In this study, the author uses a quantitative approach method and the data used in this study is secondary data from the Central Statistics Agency of Cirebon City in 2013-2022. Theresults of the research on multiple linear analysis between the variables ofUnemployment (X1) and Inflation (X2) on Economic Growth (Y), , the regression equation Y = 8.282 + -0, 364X1 + 0.1084X2+ e, this means that in the context of this model, changes in unemployment and inflation do not have a significant impact on economic growth (Y). The value of the coefficient of determination (R²) of 11.3% indicates that only a fraction of the variation in economic growth is explained by the unemployment and inflation variables in this model.